1998
DOI: 10.1016/s0735-1097(97)00534-2
|View full text |Cite
|
Sign up to set email alerts
|

Likelihood of Spontaneous Conversion of Atrial Fibrillation to Sinus Rhythm

Abstract: Spontaneous conversion to sinus rhythm occurs in almost 70% of patients presenting with atrial fibrillation of <72-h duration. Presentation with symptoms of <24-h duration is the best predictor of spontaneous conversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
77
1
10

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 180 publications
(93 citation statements)
references
References 29 publications
5
77
1
10
Order By: Relevance
“…22 Our study identifies the selective subgroups of the patients who are likely to respond to ibutilide. The clinical and echocardiographic parameters associated with a high response rate include presence of CAD (77%), absence of MVD (82%), absence of markedly enlarged LA (67%), and absence of enlarged LA as well as absence of MVD (85%).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…22 Our study identifies the selective subgroups of the patients who are likely to respond to ibutilide. The clinical and echocardiographic parameters associated with a high response rate include presence of CAD (77%), absence of MVD (82%), absence of markedly enlarged LA (67%), and absence of enlarged LA as well as absence of MVD (85%).…”
Section: Discussionmentioning
confidence: 98%
“…The half-life is 2 to 12 h (mean 6 h). [20][21][22][23][24][25] Among the class III and class I antiarrhythmic agents, ibutilide is one of the most effective agents for cardioversion, and most of the patients convert to sinus rhythm within 1 h of initiation of therapy. [27][28][29][30] All patients should be monitored closely for 4 h, as there is a 2 to 3% risk of torsade de pointes and occasional hypotension.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rate of spontaneous conversion in this group might be as high as 50% over the first 48 h, 11 and even higher in patients with shorter duration of AF at admission. 12 A placebo could expose the real value of our strategy more accurately. Data from our retrospective chart review showed a similar rate of conversion.…”
Section: Discussionmentioning
confidence: 99%